UJI STABILITAS DAN IRITASI FORMULA KRIM ANTI NYERI EKSTRAK ETANOL DAUN KELOR (Moringa oleifera) - Amriani Sapra; Suwahyuni Mus; Rifka Malluka; Dwirandy Dwirandy (Jurnal Ilmiah Manuntung, 2020)
Moringa oleifera leaf contains quercetin act as an analgesic by inhibiting cyclooxygenase and lipooxygenase. These enzymes interfere synthesis of prostaglandins by arachidonic acid and lead to reduce pain. This study aimed to obtain a physically stable M/A cream formula from the lyophilized ethanol extract of Moringa leaf and to determine the irritation effect. The cream prepared with variations of cetyl alcohol concentration F1 (2%), F2 (4%,) and F3 (6%). The cream stability was determined with organoleptic, homogeneity, type of emulsion, pH, viscosity, and spreadability parameters after accelerated condition. The Irritancy test was determined to the Albino Oryctolagus cuniculus. The results showed that F1 has the best stability than F2 and F3 and showed irritation index 0,5 classified as moderate irritation.